A review on properties of Inconel 625 and Inconel 718 fabricated using direct energy deposition. (2021) - Pratheesh Kumar, S.; Elangovan, S.; Mohanraj, R.; Ramakrishna, J.R.
Abstract: Direct Energy Deposition (DED) is among the most researched and fastest-growing additive manufacturing (AM) technique. Similar to any other AM technique, the part characteristics manufactured by DED depends highly on the process input variables that in turn affects the resultant microstructure and finally influences the physio-mechanical properties of the deposited component. Recently, Inconel 625 and 718 alloys which finds critical applications in aerospace and automobile industries, has started being fabricated using metal additive manufacturing processes such as DED. The present review paper aims to present an analysis of the significant properties of Inconel 625 and Inconel 718 alloys such as tensile properties, fatigue behaviour and creep, and provide an outline of the existing relationship between mechanical characteristics and DED processing variables of the aforementioned alloys. The paper concludes by summarizing the notable results and the areas in which future studies could focus upon.